'If I were to do it all over again, should I begin with culture?' The European integration from a cultural perspective in a multi-national Grand Duchy. Issue 3 (3rd July 2019) - Lamour, Christian; Lorentz, Nathalie
ABSTRACT: The EU integration process has been experiencing a difficult time over the past 20 years. The lack of European cultural strategy to secure better interactions between static and bounded national communities is considered as one origin of the problem. However, do the mobile Europeans co-existing in the same urban place develop cultural routines favouring an EU integration? The present article explores this issue in Luxembourg, a small metropolitan state characterised by the co-presence of large national groups coming from other European member-states. The objective of the quantitative research is to find out if the practices of performing arts in this multi-national and urban society is linked to a European integration approached in terms of cross-national friendship networks and cross-border spatial mobility. The results show that some cultural practices and social groups are related to different types of cross-national ties and mobility lifestyles securing an EU integrative process.